The effects of different exercise interventions on clinical outcomes of irritable bowel syndrome and their potential mechanisms: a systematic review and network meta-analysis - Quan, Zheping; Song, Weijia; Huang, Qianting; Wang, Jiale (Frontiers in Immunology, 2026)
BackgroundIrritable bowel syndrome (IBS) is a functional gastrointestinal disorder characterized by recurrent abdominal pain or discomfort accompanied by altered bowel habits, often alongside psychological symptoms. Increasing evidence suggests that exercise interventions not only alleviate clinical symptoms but may also exert effects through modulation of the gut-immune axis. This study aims to systematically compare the effects of different exercise modalities on symptoms, quality of life, and psychological status in IBS patients, whilst exploring potential immunological mechanisms.MethodsThe PubMed, Cochrane Library, EMBASE, and Web of Science databases were systematically searched for literature from inception to June 2025, and conventional Meta-analysis and Web Meta-analysis were performed using RevMan 5.4 and R 4.3.3 software.ResultsSixteen studies were included, covering interventions such as running, moderate-intensity aerobic exercise, Pilates, yoga, and Baguazhang. Moderate-intensity aerobic exercise and Pilates demonstrated significant effects (P < 0.05) in improving depression and anxiety scores, as well as IBS-SSS and IBS-QOL scores. Running and aerobic exercise showed the best overall efficacy. Mechanistically, exercise interventions may have a synergistic effect on the brain-gut-immune axis by enhancing parasympathetic activity, modulating the HPA axis, improving gut microbiota, strengthening intestinal barrier function, and reducing systemic inflammation. This approach alleviates gastrointestinal symptoms while enhancing mental wellbeing.ConclusionVarious exercise interventions may improve clinical symptoms and quality of life in patients with irritable bowel syndrome to a certain extent, and may possess potential immunomodulatory effects. As a relatively safe and cost-effective non-pharmacological treatment, exercise holds considerable clinical application potential in the comprehensive management of irritable bowel syndrome.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251132835.